Formulation and Evaluation of Antimicrobial herbal soap of Tridax procumbens for skin care. - Sudha Rani M.V; Sravani Vardu; Jamalbi P.; Vandana M.; Dheeraj C.; Bhaskar Naik K.; Kullayappa A.C (IIUM Press, International Islamic University Malaysia, 2023)
Introduction: Tridax procumbens has great importance in traditional medicine because of it's great antibacterial and antifungal properties. It is used for treating skin diseases in many traditions. This research aims to formulate herbal soap using methanolic extract of Tridax procumbens plant leaves and evaluate its physico chemical properties.  Methods: The herbal soaps are formulated using Tridax procumbens leaf extract. The leaves were extracted by soxhlet extraction method using methanol as solvent. Four different formulations are formulated with varying doses of plant extract and  ingredients.  Results:The physical parameters like colour, odour, appearance and evaluation parameters like pH, moisture content, % alcohol insoluble matter, foam height, foam retention, % free alkali are evaluated for four formulated soaps.  Conclusion: Among four soap formulations F1 soap showed good results. Hence formulated soaps can further be standardized and used for skin diseases.